Mediators of educational differences in dementia risk later in life: evidence from the HUNT study - Teferi Mekonnen; Vegard Skirbekk; Asta Kristine Håberg; Bo Engdahl; Ekaterina Zotcheva; Astanand Jugessur; Catherine Bowen; Geir Selbaek; Hans-Peter Kohler; Jennifer R. Harris; Sarah E. Tom; Steinar Krokstad; et al. (BMC Public Health)
Abstract Despite a well-known inverse association between education and dementia risk, the mediating mechanisms are not well understood. We explored how lifestyle and health risk factors across the life-course mediate the relationship between education and dementia among adults aged 70 + years. We included 7,655 participants with dementia diagnoses and education information, using a historical cohort design linking prospective exposure data across the life course from the HUNT4 70 + Study with registry data from Statistics Norway and earlier HUNT surveys. We conducted causal mediation analysis to assess the mediating roles of occupational characteristics, lifestyle factors (smoking, physical inactivity), and health risk factors (obesity, hypertension, diabetes, hearing impairment, cardiovascular diseases, LDL cholesterol, depression, anxiety) assessed during early, middle, and late adulthood in the relationship between education and dementia in later life. Participants with lower education were more likely to have dementia with odds ratios of 1.99, 1.88, 1.83 for the model’s accounting exposure to mediators during early, middle, and late adulthood, respectively. These associations were partially mediated by the joint effect of health and lifestyle risk factors from early through late adulthood (mediated 11.55–19.50%). Health risk factors from early to late adulthood jointly mediated 6.85–13.06% of the effect of low education on dementia risk later in life. Additionally, lifestyle factors during middle and late adulthood jointly mediated 4.11–4.96% of the total effect of low education on dementia risk later in life. Educational differences in dementia risk can partly mediated by lifestyle and health factors across the life course. These findings suggest potential targets to address varying dementia risks linked to education levels.